Programming related factors influencing in learning a programming: a study on engineering students in UiTM Pulau Pinang / Rozita Kadar... [et al.] - Kadar, Rozita; Othman, Jamal; Abdul Wahab, Naemah; Shamsuddin, Maisurah; Mahlan, Siti Balqis (Unit Penulisan Dan Penerbitan JSKM, 2022)
In response to a current need, higher education institutions have begun to provide programming courses not only to computer science students, but also to non-computer science students. This is because, in recent years, understanding of computer technology and programming in a variety of areas has become necessary to meet the industry’s demand for information and communication competency. The issue is that teaching and learning computer programming languages, particularly for non-computer science students, can be difficult. Educators face challenges in getting students to comprehend programming principles and develop outstanding programming abilities in order to tackle real-world problems. Students' lack of logical, creative, and critical thinking leads to inadequacies in problem-based learning implementation. Several factors have been identified as contributing to programming language problems, including educators, students' abilities, and programming nature, and this study investigates a programming-related factor that contributes to computer programming learning challenges, as well as the students’ background knowledge. A study was conducted on engineering students in Universiti Technologi MARA in a total of 241 students involves in this study. According to the results of a mean and standard deviation study, it is found that programming-related factor were particularly effective in learning a programming. With these findings, it can be a guideline for educators in dealing with problems in learning a programming.